Older women's upper garment a study on the clothing problems and preferences of selected Filipino women over 60 years of age - Flaviano, Robenica S.
Today there have been an increasing number of Filipino women ages 60 and above. In spite of ever growing population of this age group more interest has been shown in different areas of geriatric care, particularly in the field of health and medicine, (Rodriguez, 1999) On the other hand, very little concern is given to their clothing problems and preferences. The study employed a descriptive method of research and purposive sampling was used to obtain information from the members of two organizations namely: St. Sepulcio Parish Church in Paco, Manila and Senior Citizen Association of Pandacan, Manila. The main objective of this study is to determine the clothing problems and preferences of selected Filipino women ages 60 and above. The specific purposes were to determine the profile of the respondents, in terms of age, income source and occupation, their daily activities as well as the body changes they experience with increasing age. It also sought to answer questions about their clothing problems and specific style preferences in terms of fit, comfort and style. Questions regarding style preferences are limited only to tops (blouse and shirts). Though there have been several foreign studies about women's clothing the researcher has not found any local study which specifically determine the clothing problems and preferences of women over 60 years of age. Results and findings indicated that majority of the respondents are still actively participating with activities within and outside the vicinity of their house. However, they are least involved with sports activities. With reference to changes in body contour and size, research results revealed that the five major changes they experience are having prominent abdomen, sagging bust, added weight and increase in the size of hips, waist and upper arms. In spite of increasing age, this age group still show interest in appearance and willing to extend their individual; perception about themselves. Respondents have taken into account, physical comfort and fit, design and style along with quality as their three major concerns in selecting clothes. Family members, relatives and friends are among the most influential factors in their clothing decisions. Majority of the participants' wardrobe were either bought by others or personal purchase. In terms of specific style preferences, majority of the participants preferred garments with plain short sleeves, rounded neckline, straight hemlines that are below waistline, front opening with button or zipper closure, fabrics that are made of natural materials, light in weight, soft to touch and cool to body and skin. With regards to fitting problems, majority of the respondents perceive the following as serious clothing problems: clothes that restrict range of movements, garments that are tight at the sleeve, garment with difficult to manage closures, garments that tend to emphasize weight and garments appear more tight. In general, the study has shown that older people are still active part of our society. Their willingness to share their perception about themselves shows interest in appearance and clothing. Changes in body contour and size are important determinant of which design details would be best for this age group.